Findif code simulations of OP-1.1 Wendelstein 7-X discharges - Pełka, G.; Stępniewski, W.; Zagórski, R.; W7-X Team (Вопросы атомной науки и техники, 2019)
The current development state of the finite difference, multi-fluid, 3D plasma code Findif is detailed. The code was run on four meshes prepared for the OP-1.1 wall geometry of the Wendelstein 7-X stellarator. The meshes were produced for 4 magnetic configurations; two of them are finite-beta (non vacuum). The simulated volume covers plasma edge; the computations of limiter heat load distributions were the main goal. Plasma radiation was not taken into account.